Cyber challenges and the world after post-pandemic realities - Gouveia, Luis Borges (2021)
We live in times of accelerated use and exploitation of digital in all sectors of human activity. The pandemic and its circumstances served to anchor what is most profound that digital provides: the disruption of traditional notions of time and space. The current context is one of transition, confronting old practices with their limitations and finding new avenues of application. This leads to an open setting that will be fertile for countless innovations with the capacity to transform old practices. In a digital transformation context much deeper than that of tools and support, new practices are amplified by the possibilities of electronics being replaced or complemented by quantum and thus obtaining a capacity to deal with information, with its processing, storage, and communication, at scales not easy to perceive by current standards. In this scenario, there are enough challenges and needs to keep the world centered on human activity and people – creating new hierarchies that cope with emergent networks. These cyber challenges are worth of focus to provide a more secure environment for both people and organizations to strive.